Biological effects of static electric field: Plasma/serum proteome analysis of rats. (March 2013) - Harutyunyan, Hayk; Artsruni, Gagik
<x xml:space="preserve">Abstract</x> The external static electric field (SEF) of man-made origin brings to the substantially increased SEF background in a human environment the biological activity of which is a moot question. The paper reports on rats blood plasma/serum proteome modifications by means of 1D polyacrilamide gel electrophoresis and clotting process alterations after the short- and long-term SEF exposures of 200 kV/m. The results indicate decrease of fast α1 and α2 globular proteins in plasma coinciding with clotting acceleration after the short-term SEF, and attenuation of clotting-dependent proteome modifications reflected with incomplete coagulation after the long-term SEF exposure. Increased lysozyme activity in serum unlike plasma was observed after both SEF exposures. Applied model of the high-voltage SEF environment indicates dependence of biological systems functioning on the external SEF.